Control of the chewing louse Bovicola (Werneckiella) ocellatus in donkeys, using essential oils. Issue 4 (18th February 2013) - ELLSE, L.; BURDEN, F. A.; WALL, R.
Abstract: Infestations by lice can be a significant clinical and welfare issue in the management of large animals. The limited range of commercial pediculicides available and the development of resistance have led to the need to explore alternative louse management approaches. The results of in vitro and in vivo trials undertaken to control populations of the donkey chewing louse, Bovicola ocellatus (Piaget) (Phthiraptera: Trichodectidae) using the essential oils of tea tree ( Melaleuca alternifolia ) and lavender ( Lavandula angustifolia ) are reported here. Results of contact and vapour bioassays showed that 5% (v/v) tea tree and lavender oils resulted in > 80% louse mortality after 2 h of exposure. On farms, separate groups of 10 donkeys sprayed with 5% (v/v) tea tree and lavender oil as part of their usual grooming regime showed significant reductions in louse numbers compared with a control group (0.2% polysorbate 80 in water). These findings indicate that tea tree and lavender essential oils can provide clinically useful levels of control of B. ocellatus when used as part of a grooming routine and suggest that with further development could form the basis of an easy to apply and valuable component of a louse management programme for donkeys.